Associations between health information source and childhood vaccination - Geller, Karly S.; Montaine-O'Brien, Skyler J.; Branscum, Paul W.; Reeves-Doyle, Brandy N. (Frontiers in Public Health, 2025)
The credibility of health-related information sources may influence parental decisions regarding childhood vaccinations. This study examined whether the type of health information source used by parents (verified vs. unverified) was associated with their child's vaccination outcomes. A national sample of 887 parents (55.1% male; mean age = 36.42 years, standard deviation = 12.29) completed an anonymous online survey. Participants reported demographic characteristics, primary health information sources, and whether their child received 12 vaccine recommendations by the Center of Disease Control and Prevention (CDC). Health information sources were categorized as primarily from verified (healthcare providers, scientific journals) or unverified (family/friends, social media, opinion blogs). Compared to those using unverified sources, verified source users had significantly higher odds of vaccinating their child across most vaccines, including DTaP, Hib, Hepatitis A, Hepatitis B, influenza, MMR, MCV4, pneumonia, IPV, and RV (all ps < 0.01). Verified source users also reported significantly higher overall vaccination rates (p < 0.001). These associations remained significant after adjusting for key demographic covariates (e.g., age, household size, number of children). No significant differences were found for the chickenpox or COVID-19 vaccines. Results underscore the importance of health information credibility in promoting vaccine adherence and suggest that targeted efforts to improve access to verified health information may help address childhood vaccination gaps.